EPO: Can its use in sport be detected? - Trout, G. (1999)
Erythropoietin (EPO) is a naturally occurring peptide hormone that stimulates the production of red blood cells from bone marrow. Unlike some of the other hormones that are said to be abused in sport, there is good scientific evidence that EPO does significantly enhance performance particularly in endurance sports. In addition the drug seizures at the 1998 Tour de France demonstrated that EPO is being abused on a large scale at least in cycling.There are two approaches to detecting endogenous hormone abuse, the direct and the indirect. Each approach has advantages and disadvantages and in fact they are complementary to each other. With the direct approach, a method is sought to directly analyse the hormone in the blood or urine. For this method to work it must be possible to detect and distinguish the administered hormone from that naturally circulating in the body. The indirect approach relies on measuring changes that occur in the body as a result of the administration of a hormone.To date the most promising line of research on how to detect doping with EPO has used indirect markers, which result from stimulated erythropoiesis. These markers can be altered for several days after the EPO dosage is stopped. An EPO administration trial conducted by the Australian Sports Drug Testing Laboratory and the Australian Institute of Sport has confirmed earlier work on indirect markers and provided additional markers based on whole blood parameters. We are currently developing a valid method to detect EPO doping based on a combination of these markers.